Employee and consumer satisfaction: a report on Jamuna Bank Limited, Gazipur branch - Chowdhury, MD. Saidul Islam (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.